Pattern Recognition and Machine Intelligence 4th International Conference, PReMI 2011, Moscow, Russia, June 27 - July 1, 2011. Proceedings - Kuznetsov, Sergei O.; Mandal, Deba P.; Kundu, Malay K.; Pal, Sankar K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Pattern Recognition and Machine Intelligence, PReMI 2011, held in Moscow, Russia in June/July 2011. The 65 revised papers presented together with 5 invited talks were carefully reviewed and selected from 140 submissions. The papers are organized in topical sections on pattern recognition and machine learning; image analysis; image and video information retrieval; natural language processing and text and data mining; watermarking, steganography and biometrics; soft computing and applications; clustering and network analysis; bio and chemo analysis; and document image processing.
Keywords: Computer science; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Optical pattern recognition; Computer Science; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).; Pattern Recognition; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Algorithm Analysis and Problem Complexity